Aprendizagem com qualidade no mundo do trabalho: reflexões e possibilidades - Costa, Solange Mainardi de Souza Santa Cruz (2003)
Inserted in a society in that the productive relationships more and more are characterized by the competitiveness, to guarantee a place in the ranking of the global trade, the organizations are challenged to invest in innovation and incorporation of new technologies and human resources for the continuous improvement of the quality of their products (goods and services). In response to the technological, cultural and economical transformations, several countries try to develop Programs of Total Quality (PQT) that follow the principle of the so called Japanese model. Seeking places, regional, national and world successes in marketing the organizations look for to improve their conditions competition through quality certifications, that at the present time are governed and standardized by the series of Norms ISO 9000. It is important to alert that the certification is necessary, but not enough to guarantee the quality. Also the organizations are more than places and spaces of products; in them live and work human beings, whose productive quality has to see with the quality in the other dimensions and aspects of their life. The present research intends to contribute with a reflection and a pedagogic perspective for the training programs, so that more than " trainings " (ISO 9000:1994) they would be learning "opportunities” (ISO 9000:2000). We believed to be possible to turn the quality programs more pedagogic and humanizers.